HUBUNGAN GROWTH MINDSET TERHADAP KETERLIBATAN SISWA DALAM PEMBELAJARAN DI SEKOLAH DASAR - Bela Octavia, Vira; Rofiqoh, Naili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the issue of low student engagement in elementary school classrooms in Indonesia, which hampers effective learning. The research aims to describe the level of growth mindset among elementary students, their engagement in learning, and to analyze the relationship between growth mindset and student engagement during the learning process. Employing a quantitative correlational approach, the study was conducted at SD Negeri 1 Ngabul with 29 fourth-grade students participating as the saturated sample. Data were collected using questionnaires based on Dweck’s growth mindset theory and Fredricks et al.’s engagement dimensions, covering behavioral, emotional, and cognitive aspects. The data were analyzed using Spearman’s rank correlation to determine the strength and significance of the relationship between growth mindset and student engagement. The results indicate a strong and significant positive correlation (r = 0.768, p < 0.001), with growth mindset accounting for 58.98% of the variance in student engagement. These findings suggest that students’ beliefs in their ability to develop intelligence through effort and perseverance substantially influence their active participation and emotional and cognitive involvement in learning. The study highlights the importance of fostering a growth mindset in elementary education to enhance student engagement and learning outcomes.